Are ecophysiological responses influenced by crown position in cork-oak? - Oliveira, G; Werner, C; Correia, O (Ann. For. Sci., 1996)
Montados and dehesas of Quercus ilex and Quercus suber occupy large areas in the Iberian Peninsula and are characterized by a low-density tree cover. The variability of responses within tree canopies in such open stands has been little studied. We investigated the variation of stomatal conductance within the crown of a cork-oak (Q suber L), by studying its diurnal and seasonal courses at two different heights and four directions within the canopy. Height did not strongly affect leaf response, as a consequence of the crown structure. Differences were found in microclimatic conditions and maximum stomatal conductance among directions. However, overall daily stomatal conductance was similar among different crown sections, suggesting that leaves develop different mechanisms to accomodate the microclimatic constraints which affect the particular position they occupy in the crown of cork-oak.
Keywords: cork-oak; isolated tree; microclimate; Stomatal conductance; within-crown variability

Are ecophysiological responses influenced by crown position in cork-oak? - Oliveira, G; Werner, C; Correia, O (Ann. For. Sci., 1996)
Montados and dehesas of Quercus ilex and Quercus suber occupy large areas in the Iberian Peninsula and are characterized by a low-density tree cover. The variability of responses within tree canopies in such open stands has been little studied. We investigated the variation of stomatal conductance within the crown of a cork-oak (Q suber L), by studying its diurnal and seasonal courses at two different heights and four directions within the canopy. Height did not strongly affect leaf response, as a consequence of the crown structure. Differences were found in microclimatic conditions and maximum stomatal conductance among directions. However, overall daily stomatal conductance was similar among different crown sections, suggesting that leaves develop different mechanisms to accomodate the microclimatic constraints which affect the particular position they occupy in the crown of cork-oak.
Keywords: cork-oak; isolated tree; microclimate; Stomatal conductance; within-crown variability